Socio‐demographic, health, and psychological correlates of suicidality severity in Australian adolescents. (5th November 2015) - Delfabbro, Paul H.; Malvaso, Catia; Winefield, Anthony H.; Winefield, Helen R.
Abstract: Objective: Few studies have examined whether factors related to suicide ideation alone are also related to suicide plans and attempts. The aim of this study was to examine the psychological and social factors associated with different levels of suicide risk in Australian adolescents. Method: A sample of 2, 552 young people aged 14–16 years completed a detailed survey that included demographic, social, and psychological indicators as well as a four‐tier measure of suicidality: occasional ideation, regular ideation, suicide plans, and suicide attempts. Separate statistical models were developed for each level of suicide risk as well as an overall multinomial logistic regression to compare more severe levels of suicidality against occasional ideation. Results: The results showed that while most well‐established predictors were indicative of elevations of each level of suicide risk, only some factors predicted suicide attempts. The highest suicide attempt risk was observed in girls, those who smoked, had romantic relationships, and who had poorer health. Students with concerns about their weight, who used marijuana, who had more negative mood states, and who were in romantic relationships were more likely to have suicide plans. Conclusions: The results suggest that the identification of young people at highest risk of suicide attempts can be enhanced by focusing on specific indicators, including gender (females higher), smoking and marijuana use, and declines in physical health.